Leadership and Employee Performance: A Motivational Perspective - Jusdijachlan, Jusdijachlan; Ridwan, Susan (Dinasti International Journal of Digital Business Management, 2023)
Leadership in the Kiaracondong District Environment, Bandung City, it turns out that the majority of employees gave quite good responses; employee work motivation in the Kiaracondong District of Bandung City can generally be said to be good; The performance of employees in the Kiaracondong District of Bandung City is currently considered good. Leadership and Work Motivation simultaneously influence employee performance in the Kiaracondong District, Bandung City. However, partially dominant leadership influences performance rather than work motivation. Because leadership is more dominant in influencing performance, being the first priority in improving employee performance, the Kiaracondong District Environment in Bandung City is expected to pay attention to the fact that leaders make a big contribution to improving employee performance.